What is the value of the sum?

Calculus Level 3

If α α and β β be the roots of the equation x 2 + p x + q = 0 x^2+px+q=0 , then what is the value of the sum(given α x < 1 , β x < 1 |αx|<1, |βx|<1 ) :

( α + β ) x (α+β)x- ( α 2 + β 2 2 ) x 2 + (\dfrac{α^2+β^2}{2})x^2+ ( α 3 + β 3 3 ) x 3 (\dfrac{α^3+β^3}{3})x^3- ...... ?

[Here ln(.) means natural logarithm, that is log to the base e]

l n ( 1 p x + q x 2 ) ln(1-px+qx^2) l n ( 1 q x + p x 2 ) ln(1-qx+px^2) l n ( 1 + q x + p x 2 ) ln(1+qx+px^2) l n ( 1 + p x + q x 2 ) ln(1+px+qx^2)

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Karan Chatrath
Jul 22, 2019

Consider the following infinite series:

1 1 + z = 1 z + z 2 z 3 + \frac{1}{1+z} = 1 - z + z^2 -z^3 + \dots

Where z < 1 \mid z\mid < 1

Integrating both sides from 0 0 to z z gives:

ln ( 1 + z ) = z z 2 2 + z 3 3 z 4 4 + \ln(1+z) = z - \frac{z^2}{2} + \frac{z^3}{3} - \frac{z^4}{4} + \dots

Where z < 1 \mid z\mid < 1

Now the given series can be rewritten as:

S = ( ( α x ) ( α x ) 2 2 + ( α x ) 3 3 ) + ( ( β x ) ( β x ) 2 2 + ( β x ) 3 3 ) S = \left((\alpha x) - \frac{(\alpha x)^2}{2} + \frac{(\alpha x)^3}{3} - \dots\right) + \left((\beta x) - \frac{(\beta x)^2}{2} + \frac{(\beta x)^3}{3} - \dots\right)

Now, the pieces of information missing in the problem statement are that α x < 1 \mid \alpha x\mid < 1 and β x < 1 \mid \beta x \mid < 1 . Assuming that these two conditions hold, the above-derived formulas are applied, leading to:

S = ln ( 1 + α x ) + ln ( 1 + β x ) S = \ln(1+\alpha x) + \ln(1+ \beta x)

S = ln ( 1 + ( α + β ) x + α β x 2 ) S = \ln(1+ (\alpha + \beta)x + \alpha \beta x^2)

Using the given information in the problem statement, it can be deduced that the sum and product of roots of the given quadratic equation are:

α + β = p \alpha + \beta = -p α β = q \alpha \beta = q

Therefore, the result is finally,

S = ln ( 1 p x + q x 2 ) \boxed{S = \ln(1 -px + qx^2)}

The information which needs to be added to the problem statement are the conditions that α x < 1 \mid \alpha x\mid < 1 and β x < 1 \mid \beta x \mid < 1 .

You are right. Modifying it.

A Former Brilliant Member - 1 year, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...